A study of isolated hyperglycemia (blood glucose ≥155 mg/dL) at 1-hour of oral glucose tolerance test (OGTT) in patients with β-transfusion dependent thalassemia (β-TDT) followed for 12 years : 1-hour post-load plasma glucose (1-h OGTT) in β-thalassemia major - De Sanctis, Vincenzo; Soliman, Ashraf; Tzoulis, Ploutarchos; Daar, Shahina; Pozzobon, Gabriella Cinzia; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2021)
Objective: Subjects with normal glucose tolerance (NGT) but 1-hour post-load plasma glucose (1-h OGTT) ≥ 155 mg/dl (8.6 mmol/L; H-NGT) have an increased risk for developing Type 2 diabetes mellitus (T2DM), determining a new risk factor category with deeper metabolic impairment. The aim of this study was to evaluate the H-NGT as a diagnostic predictor of future dysglycemia in β-transfusion dependent thalassemia (β-TDT). Indices of insulin secretion and insulin sensitivity derived at baseline from OGTTs, were also reviewed. Study design and methods: OGTT and indices of insulin secretion and insulin sensitivity, derived at baseline during OGTT, in 17 β-TDT with H-NGT and 29 β-TDT with normal OGTT (NGT) and without H-NGT followed for 12 years were studied. Results: H-NGT was associated with decreased insulin sensitivity and progressive deterioration of glucose tolerance. At baseline, serum ferritin and serum alanine aminotransferase (ALT) levels were higher in patients with H-NGT compared to patients with NGT. A strong correlation was observed between ALT and 1-hour plasma glucose value during OGTT in the total group of 36 patients . Compliance to iron chelation therapy was poor in β-TDT patients with H-NGT. An inverse correlation was found between 1-hour plasma glucose value during OGTT and insulin secretion-sensitivity index-2 (ISSI-2) (r: -0.3298; p: 0.025), between ISSI-2 and ALT (r: -0.3262; p: 0.027), and between 1-hour plasma glucose value and ISSI-2 (r: -0.537; p: 0.005) in the whole group of β-TDT patients enrolled in our study. Conclusions: This retrospective study displayed that finding an isolated high 1-hour post-load glucose level (≥155 mg/dL; H-NGT) during the OGTT may serve as a simple biomarker to detect high-risk patients, with chronic liver disease and/or iron overload, who need periodic glycemic surveillance. Measuring the ISSI 2 represented another valuable predictive marker in the assessment of glycemia in these patients.